Blind quality assessment of image and speech signals - Li, Qiaohong (2017)
Quality assessment of multimedia signals is of great interest to the researchers and practitioners in signal processing community. As most multimedia services and systems are provided for human consumption, it is of great importance to reproduce human judgement of perceived quality for objective quality assessment methods. Among all kinds of these methods, no-reference or blind methods that operate solely on the distorted signals are most desirable as the reference signals are not always available in many practical applications. However, blind quality assessment is a very challenging task due to the various distortion types and diverse content properties. In this thesis, I present a series of works on designing better blind models to automatically estimate perceptual quality of image and speech signals for modern multimedia systems.